Microbiome and response surface methodology analyses reveal Acetobacter pasteurianus as the core bacteria responsible for aerobic spoilage of corn silage (Zea mays) in hot and humid areas - Bai, Rui; Li, Haiping; Chen, Shiyong; Yuan, Xianjun; Chen, Youjun; Huang, Yanling; Zhou, Qingping; Guan, Hao (Frontiers in Microbiology, 2024)
Introduction Weak aerobic stability is a notable challenge for whole-plant corn silage, particularly in hot and humid regions. Acetobacter is commonly regarded as an indicator of aerobic deterioration in silage, yet its precise role in fermentation and during aerobic exposure, as well as the factors that promote its growth, remain insufficiently understood. Methods In this study, whole-plant corn silage was prepared using a bagged method with controlled dry matter (DM) content at 20%, 25%, and 30%, and initial concentrations of A. pasteurianus at 40%, 50%, and 60%. The silage was stored for 60 days under varying temperatures (20°C, 30°C, and 40°C). Following the anaerobic storage phase, the silage was exposed to air at room temperature (20-25°C) for 7 days, both with and without A. pasteurianus inoculation. Results The results demonstrated that A. pasteurianus did not impact the nutritional value of the silage during anaerobic fermentation, maintaining a low pH (< 3.80). However, during aerobic exposure, the presence of A. pasteurianus significantly reduced the aerobic stability of the silage. The microbial community shifted from primarily Klebsiella species initially to Lactobacillus and Acetobacter species post-ensiling. During the aerobic exposure phase, A. pasteurianus and A. fabarum became the dominant species. Response Surface Methodology (RSM) analysis identified optimal conditions for the proliferation of A. pasteurianus during the aerobic phase, which occurred at 28°C, 25% DM, and 52% initial concentration at 3 ml/kg. Discussion These findings confirm that A. pasteurianus plays a critical role in reducing the aerobic stability of whole-plant corn silage. Additionally, the study identifies the optimal conditions that favor the proliferation of A. pasteurianus, offering valuable insights for the development of strategies to prevent and control this bacterium, thereby improving the aerobic stability of silage in hot and humid regions.